Gambaran Perilaku Seksual Pranikah pada Remaja - Hesty Ningrum; Wahyuni, Sri (Pro Health Jurnal Ilmiah Kesehatan, 2023)
Adolescents are a group that is vulnerable to promiscuity which has negative impacts, including unwanted pregnancies, drugs, sexually transmitted infections, HIV/AIDS. According to the Indonesian Ministry of Health, in 2019, the incidence of HIV/AIDS was in the productive age population, namely with an age range of 15-49 years, with a high chance of transmission occurring in adolescents. Observation results show that in Sulursari Village there are several internet cafes, karaoke places, markets, terminals, which are used by teenagers aged 15-19 years to perform sexual behavior. This study aims to determine the factors associated with premarital sexual behavior in adolescents in Sulursari Village, Gabus District, Grobogan Regency. The method used is quantitative with observational analytical research with a cross sectional approach. The subjects in this study were adolescents aged 15-19 years in Sulursari Village with a population of 313 people, and the research sample was 175 people. The sampling technique is simple random sampling. Analysis of the data used Fisher’s test. Results respondents who have premarital sexual behavior are more in respondents who have poor knowledge of 28.0%, respondents who have premarital sexual behavior are more in percentage of respondents whose families are less supportive, including the prevention of premarital sexual behavior, which is (31.3%) , respondents who have premarital sexual behavior are higher in respondents with low religious levels, namely 66.7%, respondents who have premarital sexual behavior are higher in respondents who get exposure to pornography through mass media, namely (58.3%). And there is a relationship between the level of knowledge (0.002), family support (0.006), religious values ​​(0.0001), and exposure to pornography (0.0005) with premarital sexual-related behavior. Conclusion There is a relationship between the level of knowledge, family support, religious values, and exposure to pornography, with premarital sexual behavior.   ABSTRAK                 Remaja merupakan kelompok yang rentan terhadap pergaulan bebas yang berdampak negatif seperti kehamilan tidak di inginkan, narkoba, infeksi menular seksual HIV /AIDS. Menurut Kementrian Kesehatan RI tahun 2019, kejadian HIV/AIDS berada pada penduduk usia produktif pada rentang usia 15-49 tahun, dengan peluang penularan tinggi terjadi pada usia remaja. Hasil observasi menunjukkan di Desa Sulursari terdapat beberapa warnet, tempat karaoke, pasar, terminal, yang digunakan remaja usia 15-19 tahun untuk melakukan perilaku seksual. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan perilaku seksual pranikah pada remaja di Desa Sulursari Kecamatan Gabus Kabupaten Grobogan. Metode yang digunakan kuantitatif dengan penelitian analitik observasional dengan pendekatan cross sectional. Subjek penelitian adalah remaja usia 15-19 tahun di Desa Sulursari dengan populasi sebesar 313 orang, sampel penelitian 175 orang. Teknik pengambilan sampel simple random sampling. Analisis data yang digunakan uji fisher. Hasil penelitian menunjukkan responden yang berperilaku seksual pranikah lebih banyak pada responden yang mempunyai pengetahuan kurang baik sebesar 28,0%, responden yang berperilaku seksual pranikah lebih banyak persentasenya pada responden yang dalam keluarganya  kurang mendukung termasuk dalam  pencegahan perilaku seksual pranikah sebesar (31,3%), responden yang berperilaku seksual pranikah lebih tinggi pada responden yang tingkat religiusnya rendah yaitu 66,7 %, responden yang  mempunyai perilaku seksual pranikah lebih tinggi pada responden yang mendapatkan paparan pornografi melalui media massa yaitu (58,3%). Terdapat hubungan antara tingkat pengetahuan (0,002), dukungan keluarga (0,006), nilai religius (0,0001), serta paparan pornografi (0,0005) dengan perilaku terkait seksual pranikah. Simpulan Terdapat hubungan antara tingkat pengetahuan, dukungan keluarga, nilai religius, serta paparan pornografi, dengan perilaku seksual pranikah.